Callus Induction and Shoot Formation for Mexican Red Bean (Phaseolus vulgaris L.) Pinto Cultivar in Vitro - Al-Saedi, Rasha K. Mohammed; Abdulhalem, Ansam G. (Iraqi Journal of Science, 2020)
The current study aimed to adopt a method for inducing callus cells and regenerating the important common red bean using different types of growth regulators such as N6-benzylaminopurine (BAP), Naphthalene acetic acid (NAA), and Thidiazuron (TDZ). Different types of common bean pinto cultivar explants, such as internodes, cotyledons and roots, were inoculated on Murashige and Skoog medium (MS) provided with different combinations of plant growth regulators, including 1- BAP (5 mg/l) 2-BAP (4.5 mg/l) NAA (0.5 mg/l), 3- BAP (4.5 mg/l), and TDZ (0.1mg/l). Callus was initiated on MS culture medium supplied with 5 mg/l BAP for all explants (internodes, cotyledons, and roots) at 50, 20, and 10% respectively, while adding NAA with 0.5mg/l showed a low percentage of callus (30%) only in the internode explants. Optimum results were obtained by growing the internodes on MS medium with 4.5 mg/l BA and either 0.5 mg/l NAA or 0.1 mg/l TDZ, transplanting the derived shoots into internodes and cotyledons with 70 and 10% respectively. This study concludes that the internodes as explants have the best growth results.